2021
DOI: 10.2106/jbjs.oa.21.00011
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Nonoperatively Treated Pediatric Supracondylar Humeral Fractures at the Nkhotakota District Hospital, Malawi

Abstract: Background: Displaced supracondylar humeral fractures (SCHFs) benefit from closed reduction and percutaneous pinning. In Malawi, many SCHFs are treated nonoperatively because of limited surgical capacity. We sought to assess clinical and functional outcomes of nonoperatively treated SCHFs in a resource-limited setting. Methods:We retrospectively reviewed all patients with SCHFs treated at Nkhotakota District Hospital (NKKDH) in Malawi between January 2014 and December 2016. Patients subsequently underwent clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 57 publications
(76 reference statements)
0
3
0
Order By: Relevance
“… 37 , 38 In addition, nonsurgical treatment of displaced supracondylar humerus fractures results in unacceptably high rates of clinical complications and functional impairments but remains the standard of care in Malawi. 15 We observed that 95% of patients in our cohort with supracondylar humerus fractures were treated nonsurgically. Of note, less than 15% of supracondylar humerus fractures presented ≥2 days, and only 4% presented over 10 days from the time of fracture.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“… 37 , 38 In addition, nonsurgical treatment of displaced supracondylar humerus fractures results in unacceptably high rates of clinical complications and functional impairments but remains the standard of care in Malawi. 15 We observed that 95% of patients in our cohort with supracondylar humerus fractures were treated nonsurgically. Of note, less than 15% of supracondylar humerus fractures presented ≥2 days, and only 4% presented over 10 days from the time of fracture.…”
Section: Discussionmentioning
confidence: 71%
“… 11 Proper fracture care, including appropriate surgery, can prevent long-term disability. 12 13 14 15 However, Malawi has insufficient surgical capacity to provide basic orthopaedic surgery to all citizens who need it. 16 Fracture care in Malawi's public sector is provided free of charge to patients through government and donor funding at 25 district hospitals and four urban central hospitals, with >90% of fractures managed in rural district hospitals by orthopaedic clinical officers (OCOs).…”
mentioning
confidence: 99%
See 1 more Smart Citation